2003
DOI: 10.1023/b:pitu.0000004798.27230.ed
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life in Patients with a Pituitary Adenoma

Abstract: A validated quality of life (QOL) measure, the SF-36 questionnaire, was used to assess patients' perception of the impact of a pituitary adenoma, prior to treatment, on his or her physical and mental functioning. Of 270 new patients evaluated for pituitary disease at the University of Virginia Pituitary Clinic, 168 met the criteria for inclusion (pituitary hormone hypersecretion and/or pituitary adenoma) into this prospective study. Results of the SF-26 questionnaire in 36 patients with acromegaly, 42 patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

24
140
1
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 207 publications
(166 citation statements)
references
References 15 publications
24
140
1
1
Order By: Relevance
“…Although most reports on QoL using generic questionnaires in NFPA describe a low QoL after treatment (7,11,41,75,76), there are also descriptions of normalization of QoL, after successful treatment, attaining scores comparable to those seen in a healthy population (77,78). As already mentioned, compared to that of other pituitary adenoma patients, QoL of NFPA patients was similar to that of patients treated for prolactinoma, and better than that of patients diagnosed with CD and acromegaly (11,39,79,80).…”
Section: Non-functioning Pituitary Adenomasmentioning
confidence: 82%
See 1 more Smart Citation
“…Although most reports on QoL using generic questionnaires in NFPA describe a low QoL after treatment (7,11,41,75,76), there are also descriptions of normalization of QoL, after successful treatment, attaining scores comparable to those seen in a healthy population (77,78). As already mentioned, compared to that of other pituitary adenoma patients, QoL of NFPA patients was similar to that of patients treated for prolactinoma, and better than that of patients diagnosed with CD and acromegaly (11,39,79,80).…”
Section: Non-functioning Pituitary Adenomasmentioning
confidence: 82%
“…Having undergone treatment with radiotherapy is also associated with worse QoL scores in acromegaly, although it is unknown whether this is due to a more aggressive disease requiring multimodal treatment for control, or due to the irradiation effect itself (41,42). Other parameters identified as markers of worse QoL in acromegaly are being older (10, 43), being female rather than male (44), having coexisting diabetes mellitus (43), having a higher BMI (10), having a longer disease duration (10), or becoming GH-deficient after the treatment for acromegaly, usually induced by prior radiotherapy (43,45).…”
Section: Acromegalymentioning
confidence: 99%
“…Johnson et al (26) have shown that quality of life is decreased in non-operated NFMA patients. From the current literature, it is unclear whether treatment of pituitary tumor will improve the quality of life.…”
Section: Non-functioning Pituitary Macroadenomasmentioning
confidence: 99%
“…They clearly found that patients with a pituitary adenoma do have an impaired QoL that should be routinely assessed in conjunction with endocrine and anatomic studies before and after treatment (4).…”
Section: Introductionmentioning
confidence: 99%